FACTORS RELATED TO PENDING CLAIM IN INDONESIAN NATIONAL HEALTH INSURANCE (JKN): A SYSTEMATIC REVIEW - Semarajana, I Nyoman Gede; Soewondo, Prastuti (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The number of Indonesian National Health Insurance (JKN) member is increasing every year. It is bringing impact to the hospital and Social Security Organizing Agency (BPJS) of health. The hospital finances will face problem if BPJS of health pending or giving a smaller number of claims paid to the hospital. The hospital will get problem with employee payroll, payment of specialist medical services, drugs availability, and maintenance of hospital facilities and medical equipment. This study aims to analyze factors related to pending BPJS claim in Indonesian National Health Insurance. Methods: This study was a systematic review used PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyses) guidelines. Data obtained from journal database of Google Scholar that published between 2014-2019. The relevant studies must include factors related to pending claim in JKN. Results: The search found out 217 studies, of which 84 studies used English and Indonesia language and only 5 studies that eligible for this study. The 5 studies showed factors related to pending claim in JKN were human resources, administration, regulation, facilities, external and evaluation factors. Human resources factor more likely appeared as cause for pending BPJS claim. Conclusion: Factors related to pending claim in JKN were human resources, administration, regulation, facilities, external and evaluation factors. Human resources was the factor that most influenced for pending BPJS claim. The hospital must create strategies to overcome the factors that cause pending claim. The government should create a policy that can help BPJS of health overcome the deficit and protect the patients from facing decrease in the quality of hospital services.